1991
DOI: 10.1111/j.1467-2494.1991.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Striae gravidarum with a topical formulation. A double blind trial

Abstract: Synopsis A prophylactic antistriae cream (Centella asiatica extract, alpha-tocopherol, and collagen-elastin hydrolisates) was assessed by a double blind trial in 80 pregnant women. In the placebo group 22 women (56%) presented striae, whereas in the treated group only 14 women (34%) developed striae in this pregnancy; this difference was significant (p < 0.05; chi(2) test). An arbitrary score was designed to assess the intensity of striae (from 0 to 3); this score was 1.42 (sd 0.5) in the treated group and 2.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
6

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 5 publications
1
48
1
6
Order By: Relevance
“…Many creams have been used to prevent SG, but most have been found to be ineffective [3]. A cream containing Centella asiatica tested in clinical trials was found to be effective and resulted in a 60% reduction in SG in one study [4,5]. However, this product is not readily available in most countries.…”
Section: Introductionmentioning
confidence: 99%
“…Many creams have been used to prevent SG, but most have been found to be ineffective [3]. A cream containing Centella asiatica tested in clinical trials was found to be effective and resulted in a 60% reduction in SG in one study [4,5]. However, this product is not readily available in most countries.…”
Section: Introductionmentioning
confidence: 99%
“…CentellaAsiatica(GotuKola)Ekstresi: Mallol ve ark. yaptığı çift kör klinik çalışmada, 40 kişilik plesebo grubunun (22) %56'sında, 40 kişilik tedavi grubunun (14) %34'ünde stria geliştiği saptanmış(p<0,05) 22 . Cocoa Butter (Kakoa Yağı): 2008 yılında yapılan, çok merkezli, çift kör, plasebo kontrollü, klinik çalışmada 91 hastaya cocoa butter, 84 hastaya plasebo uygulanmış.…”
Section: Stiriagravidarumunclassified
“…Gute Ergebnisse zur Prophylaxe von Schwangerschaftsstreifen brachte die topische Anwendung von Centella asiatica, einer Heilpflanze der traditionellen Medizin [24]. Studien über die lokale Anwendung von 20%iger Glykolsäure in Kombination mit 0,05%igem Tretinoin bzw.…”
Section: Fazit Für Die Praxisunclassified